Spleen tyrosine kinase inhibition mitigates radiation-induced lung injury through anti-inflammatory effects and downregulation of p38 MAPK and p53 - Zhang, Guoxing; Sun, Ni; Li, Xiaohua (Frontiers in Oncology, 2024)
BackgroundTo explore new modulatory intervention targets for radiation-induced lung injury, bioinformatics analysis technology was used to search for the core driving genes in the pathogenesis of radiation pneumonitis, and the results were verified by a radiation-induced murine lung injury model to find possible new targets for the treatment of radiation lung injury.MethodGene Expression Omnibus Database was used to identify differentially expressed genes in radiation pneumonitis. DAVID database was used for gene ontology (GO) and Kyoto Encyclopedia of Genes and Genome (KEGG) enrichment analysis. Gene Set Enrichment Analysis was used to analyze abnormal expressions. Protein–protein interaction networks were constructed using STRING and Cytoscape. Discovery Studio 4.5 software was used to find the preferred inhibitor of the specific gene. A radiation-induced lung injury model was induced in female C57BL/6N mice. The specific inhibitors were administered by intraperitoneal injection 24 h before and for 7 consecutive days after radiation. Lungs were harvested for further analysis 14 days and 10 weeks post-irradiation.ResultsWe screened Syk as one of the most important driver genes of radiation pneumonitis by bioinformatics analysis and screened the preferred Syk inhibitor fostamatinib from the drug database. Syk was highly expressed in irradiated lung tissue, and fostamatinib inhibited the level of Syk expression. Syk inhibitor significantly alleviated the radiation-induced lung injury and downregulated the increased expression of p38 MAPK, p53, IL-1β, and IL-6 in lung tissue at 2 weeks after radiation. The levels of TGF-β, COL1A1, and α-SMA and degree of pulmonary fibrosis at 10 weeks after radiation were also decreased by Syk inhibitor.ConclusionSyk inhibitor may have a potential to be used as a targeted drug to mitigate radiation pneumonitis and inhibit radiation-induced pulmonary fibrosis.